Peningkatan Self Empowerment Klien Diabetes Militus Tipe 2 dengan Pendekatan Health Action Proces Approach - M.Elyas Arif Budiman; Said Mardijanto; Ah. Yusuf (FORIKES, 2020)
Diabetes mellitus is a chronic disease that requires the individual ability of patients to approve the process of disease management. Individuals with DM must take great responsibility for the care of themselves in the treatment of their illness. Empowerment of individuals to control independent life and make choices about self empowerment. Self empowerment in DM patients can be improved through the approach of the health action process approach which is a concept of a patient that is believed to be done by increasing the intention through the motivational phase to realize the intention to action. The purpose of this study was to determine the increase in self empowerment of people with type II diabetes mellitus with a health action approach. This study used a pre-experimental study using a control-group pre-test-post-test design. The population was 64 with type 2 diabetes mellitus patients. The sample were 32 people in the experimental group and 32 people in the control group, selected by purposive sampling. Self empowerment using diabetes empowerment scale (DES) questionnaire in accordance with the characteristics of the research subjects. Data analysis was performed with the Wilcoxon statistical test signing the rank test and Mann-Whitney with the result of p value of 0.000 < 0.05 so that there were differences between the experimental and control groups. The results in this study were DM clients who have a good increase in self empowerment are clients who have the motivation and ability to recover from illness. Keywords: diabetes mellitus; self empowerment; health action process approach ABSTRAK Diabetes mellitus merupakan salah satu penyakit kronis yang memerlukan kemampuan individu dari klien untuk mematuhi penatalaksanaan proses penyakit. Individu dengan penyakit DM mempunyai tanggung jawab yang besar untuk mengatur dirinya sendiri dalam melakukan perawatan pada penyakitnya. Kemampuan individu untuk mempunyai kontrol atas hidup mereka sendiri dan menentukan pilihan mengenai kesehatan disebut self empowerment. Self empowerment pada klien DM dapat ditingkatkan melalui pendektan Health Action Process Approach yang merupakan suatu konsep pendekatan terhadap klien yang meyakini bahwa untuk mengubah perilaku seseorang dapat dilakukan dengan cara meningkatkan niat melalui motivational phase untuk membentuk niat menjadi action. Tujuan penelitian ini adalah untuk mengetahui peningkatan self empowerment klien diabetes militus tipe II dengan pendekatan Health action proces approach. Penelitian ini menggunakan pre-eksperiment dengan pendekatan control-group pre-test-post-test design. Populasinya adalah klien diabetes mellitus tipe 2 dengan jumlah 64 responden. Ukuran sampel adalah 32 orang pada kelompok eksperimen dan 32 orang pada kelompok kontrol dengan pengambilan sampel menggunan teknik purposive sampling. Self empowerment diukur menggunakan kuesioner Diabetes Empowerment Scale (DES) yang dimodifikasi sesuai dengan karakteristik subjek penelitian. Analisis data dilakukan dengan uji statistik Wilcoxon signed rank test dan Mann-Whitney dengan hasil p value signifikansi 0,00 < 0,05 sehingga ada perbedaan antara kelompok eksperimen dan kelompok kontrol. Hasil dalam penelitian ini adalah bahwa klien DM yang memiliki peningkatan self empowerment yang baik adalah klien yang memiliki motivasi dan kemaun untuk sembuh dari penyakit. Kata Kunci: diabetes mellitus; self empowerment; health action proces approach